Intramedullary spinal cord tumours: a clinical outcome and radiological follow-up study (Swiss Medical Weekly, 2001)
Principles: Intramedullary spinal cord tumours are rare. The long-term results depend on their varying natural histories and the surgical approach. Less extensive tumour resection avoids greater postoperative neurological impairment without a negative impact on postoperative outcome.Methods: Twenty-seven patients who underwent a total of 34 surgical interventions (including 7 reoperations) were clinically and radiologically reinvestigated. Histology revealed 19 glial, 4 nonglial and 4 miscellaneous tumours.Results: Postoperative long-term clinical follow-up (mean 62 months postoperatively) in 25 patients revealed functional improvement in 2 cases, stable conditions in 17 and deterioration in 6. Although there was residual tumour on MRI in 19 of the 22 patients reexamined, stable radiological studies were seen in 15 cases. Despite the high percentage of partial resections or biopsies, good long-term clinical results were found in 19 patients (70%).Conclusion: The long-term outcome depends on tumour biology and the type of surgery. For low-grade astrocytomas we propose partial resection without incurring the risk of major postoperative neurological deficits, with semi-annual and, after 5 years, annual follow-up. Despite the fact that ependymomas are amenable to complete surgical resection, this was achieved in only one of six cases in this series. Postoperative MRI follow-up of intramedullary tumours must be protracted, as most of these tumours are slow-growing. An increase in the extent and intensity of contrast enhancement of the tumours was defined as tumour recurrence or progressive tumour growth.